GESTATIONAL LOSS: EMOTIONAL AND LEGAL ASPECTS (American International Journal of Humanities, Arts and Social Sciences, 2021)
This study attempts to verify the conditions of mothers who have gone through gestational loss. It is designed according to semi-structured interviews of affected mothers. Through semi-structured recorded interviews, directed questions were asked to ascertain perceptions that they were living through at that moment, about their adaptation to daily life, and about their mourning process and the quality of their professional activities. From the interviews, eight categorizations were created: symptoms of mourning; the time to return to work and daily routines; lack of societal recognition of mourning; mourning and spirituality; seeking of healthcare support; the fathers’ pain; the need of someone; who is this baby? And the following feelings were documented from the interviews: feelings of losing control of one’s life; broken dreams; feelings of incompleteness, guilt, and personal defeat; feelings of inferiority as a woman; subjective losses; losses in identity and eroticism; a woman’s role in society. Lastly, the study examines how gestational loss is unrecognized and unsupported by legislation, exposing a weakness in workers’ rights and unequal treatment regarding gender.